A shadow in the night: Around Cadiz's constitutionalism and New Granada [Una sombra en la noche: En torno al constitucionalismo gaditano y la Nueva Granada] (2014)
This paper will address the issue of relations between the Constitution of Cadiz with the New Granada from four points. (I) The relevance of another reflection about the connections between the Constitution of Cadiz with America, in general, and New Granada, in particular, within the context of the bicentennial celebrations. (II) The type of relationship that took place between the Constitution of Cadiz and the constitutions of the independence's period, especially with the ones of the first republic (1811-1815). (III) The normative value that had the Constitution of Cadiz in different provinces of the New Granada, concluding that any answer to the above question may not fall on absolutes, black or white, but in a wide shade of gray. (IV) The different looks that received the Constitution of Cádiz during the war of independence in the New Granada. It will finally conclude that the Constitution of Cadiz cannot be considered as the first Colombian Constitution, although it has been for the Viceroyalty of the New Granada.